Flexural strengthening of reinforced low strength concrete slabs using prestressed NSM CFRP laminates - Hosseini, Mhoammadreza Mostakhdemin (2016)
The effectiveness of the Near Surface Mounted (NSM) technique with prestressed CFRP (carbon fiber reinforced polymer) laminates for the flexural strengthening of reinforced concrete (RC) slabs of low strength concrete was assessed. Four RC slabs were tested, a reference slab (without CFRP), and three slabs flexurally strengthened using NSM CFRP laminates with different prestress level of the ultimate tensile strength of the CFRP: 0%, 20% and 40%. The experimental program is described and the main results are presented and analyzed in terms of the structural behavior of the RC slabs, failure modes and performance of the NSM technique with prestressed CFRP laminates. The results show that prestressing CFRP laminates with NSM technique is an effective technology to increase cracking, service, yielding and maximum loads of RC slabs made by low strength concrete. By applying NSM CFRP laminates prestressed at 20%, the cracking, service and maximum loads have increased, respectively, 258%, 123% and 125%, when the corresponding values of the reference slab are taken for comparison purposes, while 400%, 190% and 134% were the increase when applying laminates prestressed at 40%. Using available experimental results obtained with the same test setup, but using RC slabs of higher strength concrete, it can be concluded that as minimum is the concrete strength as more effective is the NSM technique with prestressed CFRP laminates in terms of serviceability limit states. A numerical strategy was used to evaluate the load-deflection of the tested RC slabs and to highlight the influence of the percentage of CFRP, the percentage of tensile longitudinal bars and the elasticity modulus of the CFRP on the effectiveness of the NSM technique with prestressed CFRP laminates for the flexural strengthening of RC slabs, by performing a parametric study.